How is the Choice of Owning Life Insurance Related to Consumer Protection? Consumer Finance, Consumer Protection, Insurance - Campbell, B. Steele; Kalenkoski, Charlene (International Journal of Business and Social Science Research, 2022)
In the United States, no two states are completely alike in how they govern their citizenry or regulate commerce within their borders. These differences may be used to examine the effects of various laws by contrasting the differences in the way each state attempts to resolve a perceived problem and the resulting outcome. The following paper examines the relationship between consumer purchasing behavior and statutory solutions enacted to combat the perceived problems of unfair and deceptive acts. The statutory solutions are Unfair and Deceptive Acts and Practices (UDAP) statutes. This paper focuses on UDAP statutes and their relationship to life insurance ownership. This paper finds that under some circumstances consumer ownership of life insurance is related to how a state chooses to protect its citizens from unscrupulous acts of persons or businesses. This article may serve as an opportunity for ethical professionals in financial services to understand how more significant levels of regulation can result in growth opportunities.